Occupational exposure to asphalt mixture during road paving is related to increased mitochondria DNA copy number: a cross-sectional study - Yiyi Xu; Christian H. Lindh; Bo A. G. Jönsson; Karin Broberg; Maria Albin (BMC, 2018)
Abstract Background Asphalt workers are exposed to polyaromatic hydrocarbons (PAHs) from hot mix asphalt via both inhalation and dermal absorption. The use of crumb rubber modified (CRM) asphalt may result in higher exposure to PAHs and more adverse effects. Our aim is to assess occupational exposure to PAHs from conventional and CRM asphalt paving by measuring PAH metabolites in urine, and to investigate the effects on mitochondrial DNA copy number (mtDNAcn) and telomere length. Methods We recruited 116 workers paving conventional asphalt, 51 workers paving CRM asphalt and 100 controls in Sweden, all males. A repeated-measures analysis included 31 workers paving both types of asphalt. Urine and blood samples were collected pre-working on Monday morning and post-working on Thursday afternoon after 4 days working. PAH metabolites: 1-hydroxypyrene (1-OH-PYR) and 2-hydroxyphenanthrene (2-OH-PH) were measured in urine by LC-MS/MS. Relative mtDNAcn and telomere length were measured by quantitative PCR. Results Conventional and CRM asphalt workers showed higher 1-OH-PYR and 2-OH-PH than controls (p < 0.001 for all). Relative mtDNAcn were 0.21 units (p < 0.001) higher in conventional asphalt workers and 0.13 units (p = 0.010) higher in CRM asphalt workers compared to controls. Relative telomere length did not differ across occupational groups, but it was positively associated with increment of 2-OH-PH (β = 0.075, p = 0.037) in asphalt workers. The repeated-measures analysis showed no difference in either increment of 1-OH-PYP, or changes in effect biomarkers (mtDNAcn or telomere length) between paving with conventional and CRM asphalt. Increment of 2-OH-PH was smaller after paving with CRM asphalt. Conclusions Road asphalt paving in open areas resulted in PAHs exposure, as shown by elevation of PAH metabolites in urine. Asphalt workers may experience oxidative stress, evidenced by alternation in mtDNAcn; however the effects could not be fully explained by exposure to PAHs from the asphalt mixture.